High-performance electron injection layers with a wide processing window from an amidoamine-functionalized polyfluorene - Stolz, Sebastian; Petzoldt, Martin; Sendner, Michael; Bunz, Uwe H. F.; Hamburger, Manuel (ACS applied materials & interfaces, 2016)
In this work, we present organic light-emitting diodes (OLEDs) utilizing a novel amidoamine-functionalized polyfluorene (PFCON-C) as an electron injection layer (EIL). PFCON-C consists of a polyfluorene backbone to which multiple tertiary amine side chains are connected via an amide group. The influence of molecular characteristics on electronic performance and morphological properties was tested and compared to that of the widely used, literature known amino-functionalized polyfluorene (PFN) and polyethylenimine (PEI). PFCON-C reduces the turn-on voltage (VON) of poly(p-phenylene vinylene) (PPV)-based OLEDs from ∼5 to ∼3 V and increases the maximum power efficiency from <2 to >5 lm W-1 compared to that of PFN. As a result of its semiconducting backbone, PFCON-C is significantly less sensitive to the processing parameters than PEI, and comparable power efficiencies are achieved for devices where thicknesses of PFCON-C are between 15 and 35 nm. Atomic force microscopy (AFM) measurements indicate that the presence of nonpolar side chains in the EIL material is important for its film-forming behavior, while Kelvin probe measurements suggest that the amount of amine groups in the side chains influences the work-function shift induced by the EIL material. These results are used to suggest strategies for the design of polymeric electron injection layers.
Gesehen am 15.05.2020